Benefits of using methimazole in comparison to hydroquinone in the treatment of Melasma (Research, Society and Development, 2021)
Facial hyperchromias are pigmentary disorders caused by an increase in melanin in a specific area of ​​the skin. Melasma is an acquired hyperchromia, clinically diagnosed, with a high rate of recurrence. Its etiopathogenesis is not fully known, including several factors that facilitate its appearance or aggravate the problem, including exposure to UV rays, genetics, pregnancy, hormonal therapies, among others. Treatment is still a challenge and for many years hydroquinone was one of the most used substances as a tyrosinase inhibitor, but it has many toxic and harmful effects on the skin and other organs. Some alternative treatments with other depigmenting agents, such as metthimazole, also for topical use, have been increasingly effective and with fewer side effects when compared to hydroquinone. This is a literature review study that consists of the existence of two objectives, which are to contextualize a problem and verify existing possibilities in the literature in the formation of the theoretical framework. Furthermore, it is a descriptive exploratory research. Articles that present melasma with the main theme and that have been published between 2009 and 2020 will be selected. Those articles published before 2009 and that have no connection with the topic will be excluded. Conclusion: the study concluded that methimazole use is safer and more effective when compared to hydroquinone, but has slower results. The importance of further research evaluating the safety and efficacy of topical methimazole use is emphasized.